Association of metabolic health phenotypes, obesity, and hepatocellular carcinoma risk. Issue 7 (July 2022) - Nasereldin, Duaa S.; White, Launia J.; Hodge, David O.; Roberts, Lewis R.; Patel, Tushar; Antwi, Samuel O.
Abstract: Background: The obesity and hepatocellular carcinoma (HCC) risk association may differ by individuals' metabolic health status. Aim: To investigate the association between obesity categories and HCC risk among individuals with different metabolic health phenotypes. Methods: A case-control study among 518 HCC cases and 1, 036 frequency-matched controls was conducted. Body mass index (BMI) was assessed before diagnosis. Pre-diagnosis data on dyslipidemia, hypertension, and diabetes were used to categorize participants as metabolically healthy or metabolically unhealthy. Participants were further categorized into metabolically healthy normal weight (MHNW), metabolically healthy overweight (MHOW), metabolically healthy obese (MHO), metabolically unhealthy normal weight (MUNW), metabolically unhealthy overweight (MUOW), and metabolically unhealthy obese (MHO). We used logistic regression to calculate multivariable-adjusted odds ratios (ORs) and 95% confidence intervals (CIs). Results: Being overweight (OR=1.68, 95%CI=1.21–2.34) or obese (OR=1.49, 95%CI=1.11–1.89) was associated with higher HCC risk. Among metabolically healthy participants, no association was found between being overweight or obese and HCC risk. However, among the metabolically unhealthy participants, being overweight (OR=1.89, 95%CI=1.31–2.72) or obese (OR=1.50, 95%CI=1.07–2.09) was associated with higher HCC risk. Compared to the MHNW phenotype, no association was found between the MHOW and MHO phenotypes and HCC risk, but the MUNW (OR=1.94, 95%CI=1.09–3.43), MUOW (OR=3.78, 95%CI=2.15–6.65), and MUO (OR=2.93, 95%CI=1.70–5.05) phenotypes were associated with higher HCC risk. Conclusion: The association between BMI and HCC appears to be restricted to individuals with underlying metabolic abnormalities.